A novel key exchange algorithm for security in internet of things - Suresh Koduru; PVGD Prasad Reddy; Padala Preethi (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Today Internet of things (IoT) interconnects any object possessing sensing and computing capabilities to the internet. In this era, increasing number of electronic devices and applications in Internet of Things (IoT) requires secured communication with low power consumption capabilities. As security is a major challenge in internet of things, it is important to design a key management solution that considers resource constrained nodes and hence key management in public key cryptography is a crucial issue. In this paper, a novel key exchange algorithm was developed and implemented on a low powered “Raspberry pi machine” to realize the overall impact it creates on the device. The performance of the proposed algorithm had shown a great improvement over the popular Diffie Hellman key exchange algorithm and a two-level security for data exchange between the parties is implemented.